A2.11 Involvement of the Nucleic Acid Recognising Toll-Like Receptors TLR7 and TLR9 in the Pathogenesis of Erosive Arthritis. (25th February 2013) - Fischer, Anita; Böhm, Christina; Saferding, Victoria; Goncalves-Alves, Eliana; Koenders, Marije; Berg, Wim van den; Herman, Sonja; Steiner, Günter
Abstract : Background: There is substantial evidence that abundant release and/or insufficient removal of endogenous nucleic acids can trigger autoimmune reactions via activation of nucleic acid recognising Toll-like receptors (TLR) such as TLR7 and TLR9, which may lead to the development of SLE and other systemic autoimmune diseases. However, in RA the involvement of these TLRs is less well understood. Interestingly, in rats with pristane-induced arthritis (PIA) disease can be transferred by T cells together with antigen-presenting-cells pre-activated with TLR7 or TLR9 agonists (Hoffmann et al, J Autoimmunity 2011; 36: 288–300). Objective: We aimed to study the role of TLR7 and TLR9 in the pathogenesis of inflammatory erosive arthritis by antagonising them in PIA and the KRN serum transfer model. Methods: Arthritis was induced in rats with the mineral oil pristane, and in C57Bl/6 mice by injection of KRN serum. Immunoregulatory oligodeoxynucleotide (ODN) sequences (IRS) antagonising TLR7 or TLR9 were applied either subcutaneously (PIA) or intra-peritoneally (KRN). A non-inhibitory ODN was used as control and PBS served as placebo. Arthritis was scored using established scoring systems, inflammation and bone erosion were quantitatively analysed by histology. Serum and cell culture cytokine levels were measured by ELISA. Results: While the TLR7 inhibitor and the control ODN showed no effect on arthritis development and severity, the TLR9 antagonist reduced arthritis severity significantly in PIA. Bone erosion was almost completely abolished, whereas it was moderately aggravated in animals treated with the TLR7 inhibitor. Furthermore, IL-6 serum levels were significantly reduced in animals treated with the TLR9 antagonist. However, these beneficial effects were only observed when the inhibitor was applied before disease onset. Moreover, neither inhibitor affected arthritis onset and severity in the serum transfer model, which is independent of the adaptive immune system. Summary and Conclusions: Inhibition of TLR9 significantly reduced inflammation and bone erosion in PIA but not in the KRN serum transfer model that reflects the late effector phase of erosive arthritis. Therefore, these results suggest important involvement of the DNA (CpG) recognising TLR9 in the initiation of autoimmune arthritis whereas nucleic acid binding TLRs do not seem to play a major role in the later phases of the disease. Antagonizing TLR9 in human RA may only act beneficial in the earliest phase of the disease.